TURBULENSI LINGKUNGAN DALAM PENYUSUNAN STRATEGI PERUSAHAAN: STUDI KASUS PADA PERUSAHAAN INDUSTRI PETROKIMIA - Sadikin Kuswanto; Sjafri Mangkuprawira; Setiadi Djohar; Aji Hermawan (School of Business, Bogor Agricultural University (SB-IPB), 2010)
The constant change and rapid growth of the business world could create turbulence in a business organization, therefore, the business professionals have to continuously increase their skill and ability to be able to maintain the existence and even improve the condition of their business in this highly competitive world. A company would reach its optimal performance when there is an alignment between its business organization and the surrounding environment filled with no strategic gap. If good strategic planning is already in place, then the other crucial aspect to be analyzed would be the external factors outside an organization. The purpose of this is to measure and understand the behaviors and effects of those external factors towards the company through threats as well as opportunities. There are five level of environment turbulence: Repetitive, Expanding, Changing, Discontinuous and Suprising. The case study in this research concludes that all seven petrochemical companies have done a consistent and continuous strategic planning. The environment turbulence level is on two grades, Expanding and Changing, however, the most dominant is Expanding. The avarage score calculation also showing the same result, Expanding.